Experiential Learning to Teach User Experience in Higher Education in Past 20 Years: A Scoping Review - Kang, Jin; Roestel, Noemi M. E.; Girouard, Audrey (Frontiers in Computer Science, 2022)
Experiential learning is an effective method to teach User Experience (UX) to Human-Computer Interaction (HCI) students. Despite its popularity, there seems to be no comprehensive overview on (1) the current use of experiential learning in UX education at universities and (2) student learning outcomes and benefits resulting from the use of experiential learning. Hence, we conducted a scoping review to provide such overview. We analyzed 45 articles published from 2000 to 2021 and we found 12 types of experiential learning employed by HCI educators: applied research project, industry/community research project, hands-on activity, role-play, interactive workshops, guest speakers, in-house work placement, internship, flipped classroom, field project, lab, and design hackathon, from most to least frequent. Twenty-four articles reported student learning outcomes and benefits: (1) enhanced UX technical knowledge, (2) applied textbook knowledge into practice, (3) acquired soft skills, (4) student satisfaction, (5) increased awareness of user diversity, and (6) increased job marketability. Overall, we advance current HCI teaching practices by providing HCI educators with a list of experiential learning types that they can adopt in their classes to teach UX.